Exploring the Effectiveness of Hybrid Learning Models in Higher Education Post-Pandemic - Riza Hamid (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study explores the effectiveness of hybrid learning models in higher education following the COVID-19 pandemic. Hybrid learning, which combines online and face-to-face instruction, became a widely adopted approach during the pandemic, and its potential to enhance student learning and engagement in the post-pandemic era is a critical area of investigation. The research aims to evaluate the impact of hybrid learning on student performance, engagement, and satisfaction, while also identifying the challenges and benefits associated with its implementation. Data were collected through a mixed-methods approach, including surveys, interviews, focus groups, and institutional data analysis. Quantitative data were analyzed to compare student performance and engagement in hybrid versus traditional learning environments, while qualitative insights were gathered from students, faculty, and administrators to understand their perceptions and experiences. The findings indicate that while hybrid learning offers significant benefits, such as flexibility and increased accessibility, it also presents challenges related to technological access, time management, and institutional support. Variability in the effectiveness of hybrid learning was observed across different academic disciplines and institutions, with some disciplines adapting more successfully than others. The study concludes with recommendations for enhancing hybrid learning practices in higher education, emphasizing the need for tailored approaches that consider disciplinary differences and institutional contexts.